Effects of caffeic acid phenethyl ester on isoproterenol-induced myocardial infarction in hypertensive rats - Oktar, Suleyman; Yilmaz, Nigar; Ilhan, Selcuk; Sahna, Engin (Taylor & Francis Inc, 2010)
[Abstract Not Available]
9th International Meeting of the International-Society-for-the-Study-of-Xenobiotics(ISSX) -- SEP 04-08, 2010 -- Istanbul, TURKEY